Two Genetically Similar H9N2 Influenza A Viruses Show Different Pathogenicity in Mice - Liu, Qingtao; Liu, Yuzhuo; Yang, Jing; Huang, Xinmei; Han, Kaikai; Zhao, Dongmin; Bi, Keran; Li, Yin (Frontiers in Microbiology, 2016)
H9N2 Avian influenza virus has repeatedly infected humans and other mammals, which highlights the need to determine the pathogenicity and the corresponding mechanism of this virus for mammals. In this study, we found two H9N2 viruses with similar genetic background but with different pathogenicity in mice. The A/duck/Nanjing/06/2003 (NJ06) virus was highly pathogenic for mice, with a 50% mouse lethal dose of 102.83 50% egg infectious dose, whereas the A/duck/Nanjing/01/1999 (NJ01) virus was low pathogenic for mice, with a 50% mouse lethal dose of >106.81 50% egg infectious dose. Further studies showed that the NJ06 virus grew faster and reached significantly higher titers than NJ01 in vivo and in vitro. Moreover, the NJ06 virus induced more severe lung lesions, and higher levels of inflammatory cellular infiltration and cytokine response in lungs than NJ01 did. However, only twelve different amino acid residues (HA-K157E, NA-A9T, NA-R435K, PB2-T149P, PB2-K627E, PB1-R187K, PA-L548M, PA-M550L, NP-G127E, NP-P277H, NP-D340N, NS1-D171N) were found between the two viruses, and all these residues except for NA-R435K were located in the known functional regions involved in interaction of viral proteins or between the virus and host factors. Summary, our results suggest that multiple amino acid differences may be responsible for the higher pathogenicity of the NJ06 virus for mice, resulting in lethal infection, enhanced viral replication, severe lung lesions, and excessive inflammatory cellular infiltration and cytokine response in lungs. These observations will be helpful for better understanding the pathogenic potential and the corresponding molecular basis of H9N2 viruses that might pose threats to human health in the future.